The Effect of Fordyce Happiness Training on the Depression of the Mothers of Premature Infants Admitted to the Neonatal Intensive Care Unit - F Barekzaei; A Navidian; N Rezaee (Iran University of Medical Sciences, 2020)
Background & Aims: The birth of a premature and sick infant leads to a severe psychological crisis for the parents. The birth of an infant is associated with numerous changes in the family function in terms of lifestyle, leisure, and relations of the family members. When an infant is born in need of medical care, these changes are intensified, and the family members experience increased mental pressure. Premature delivery and admission of the neonate adversely affects the emotional state of the mother, and one of the psychological reactions perceived by these mothers is the onset of depressive symptoms. Depressed mothers are faced with several challenges in the care of an inpatient infant, which are considered a risk factor for the deterioration of their mental health and dysfunction. Despite the advances in the quality care in neonatal intensive care units (NICUs) for infants, the psychological needs of their mothers have received less attention. The mothers of the premature infants admitted to NICUs experience various psychological issues (e.g., depression). These issues along with the physical complications of childbirth cause these women not to pay attention to their physical and mental health. Today, the identification and provision of early interventions to prevent and reduce these issues have become a priority of healthcare services in the world. The present study aimed to assess the effect of Fordyce happiness training on the depression of the mothers of the premature infants admitted to the NICUs of the medical centers in Zahedan, Iran. Materials & Methods: This quasi-experimental study was conducted in the spring and summer of 2019 on 80 mothers of the premature infants admitted to the NICUs of Zahedan. The subjects were selected via convenience sampling and divided into two groups of intervention (n=40) and control (n=40). For sampling, the researcher initially referred to the NICUs and identified the mothers of the admitted premature infants. After explaining the research objectives and obtaining written consent, the mothers who met the inclusion criteria were enrolled. The mothers of the control group were enrolled first, followed by the mothers of the intervention group in order to prevent the transfer of information in the groups. Prior to the study, the mothers were asked to complete the demographic information form and Beck depression inventory. The mothers of the intervention group received Fordyce happiness training in groups of 4-5 for six sessions every other day (45-60 minutes). Fordyce happiness training is a program designed to increase the happiness of community members, which consists of 14 cognitive and behavioral elements. In the present study, some of the components of Fordyce happiness training that were appropriate for the sample population were presented and discussed based on examples and experiences. One month after the intervention, the questionnaire was completed again. The control group received no other training than the routine educational program of the hospital, as well as the posttest simultaneous with the intervention group. Data analysis was performed in SPSS version 16 using statistical tests. Results: The minimum and maximum age of the mothers in the intervention and control groups was 15 and 31 years and 18 and 35 years, respectively. Most of the deliveries in the intervention group were natural (65%), and in the control group, the mode of delivery was equal in both groups (50%). No significant differences were observed in most of the variables between the groups, while the age of the mothers was significantly different between the groups. The analysis of covariance was used for the confounding effect of age, and the results of the analysis of covariance to adjust the effect of the pretest scores and age variable indicated a significant difference in the mean score of depression in the mothers of the preterm infants admitted to the NICU between the groups after Fordyce happiness training (P=0.0001). Therefore, the implementation of Fordyce happiness training in the intervention group could reduce the mean score of depression in the mothers. The mean score of maternal depression in the intervention group decreased from 23.72±5.81 before the intervention to 11.47±3.17 after the intervention. In the control group, the score increased from 21.82±10.58 before the intervention to 23.90±3.62 after the intervention. However, the results of independent t-test indicated that the mean score of maternal depression before intervention had no significant difference between the study groups (P=0.32), while it was considered significant after the happiness training in both the intervention and control groups (P=0.0001). Conclusion: According to the results, Fordyce happiness training could reduce depression in the mothers of the premature infants admitted to the NICU. Although the experience of childbirth is pleasant for the mother, giving birth to a premature infant and the admission of the infant could be an unpleasant experience, adversely affecting the emotional state and of the mother and giving rise to depressive symptoms. In order to maintain and promote the mental health of mothers, in addition to the care of the premature infant in medical centers, the health of the mother of the infant should also be considered. Fordyce happiness training could positively influence the reduction of depression in these mothers. Fordyce happiness training is a type of cognitive-behavioral intervention, which is used to reduce depression. This intervention enables the individual to find a more positive mindset in controlling distressing emotions and thoughts, which in turn enhances the cognition of patients by reducing depression. The reduction of depressive symptoms improves the performance of individuals in responsibilities and duties. The mothers who overcome their issues in this regard are able to participate in the care of the neonate during admission. Therefore, this training program could be implemented alongside family-oriented programs in medical centers, and it is essential to consider programs such as Fordyce happiness training to maintain and promote maternal mental health.